Modification and co-option of leaf developmental programs for the acquisition of flat structures in monocots: unifacial leaves in Juncus and cladodes in Asparagus - Nakayama, Hokuto; Yamaguchi, Takahiro; Tsukaya, Hirokazu (Frontiers in Plant Science, 2013)
It has been suggested that modification and co-option of existing gene regulatory networks (GRNs) play an important role in the morphological diversity. In plants, leaf development is one of active research areas, and the basic GRN for leaf development is beginning to be understood. Moreover, leaves show wide variation in their form, and some of this variation is thought to be the result of adaptation. Thus, leaves and leaf-like organs are an emerging and interesting model to reveal how existing GRNs give rise to novel forms and architectures during evolution. In this review, we highlight recent findings in Evo-Devo studies, especially on Juncus unifacial leaves, which are composed of lamina with abaxialized identities, and Asparagus cladodes, which are leaf-like organs at the axils of scale leaves. Based on these studies, we discuss how flat structures have evolved and morphologically diversified in shoot systems of monocot species, focusing on the modification and co-option of GRN for leaf development.